Implikasi Doktrin Imago Dei dalam Kearifan Lokal: Sebuah Kajian Kritis untuk Memperkaya Materi PAK Menurut Perspektif Jürgen Moltmann (Jurnal Pendidikan Agama dan Teologi, 2025)
This study aims to analyze the implications of the Imago Dei doctrine in Indonesian local wisdom for enriching Christian Religious Education (PAK) materials from Jürgen Moltmann's perspective. This research uses a qualitative approach with library research design and Miles-Huberman interactive analysis model. The findings reveal that Indonesian local wisdom such as pela gandong, dalihan na tolu, huma betang, and menyama braya have deep resonance with the Imago Dei doctrine, particularly in Moltmann's relational theological perspective. The integration of local wisdom with the Imago Dei doctrine brings profound theological implications including expanding understanding of fellowship (koinonia), holistic salvation, transformative leadership, and contextual spirituality. This study recommends that PAK educators develop curricula that systematically integrate local wisdom with theological foundations, use participatory pedagogical approaches, build sensitivity to cultural contexts, and create collaborative networks with traditional leaders. The integration of local wisdom with the Imago Dei doctrine is not merely a pedagogical strategy but a theological calling to realize God's Kingdom in the Indonesian context.